The typology of the “text in the text” narrative model in the novels “The Master and Margarita” by M. Bulgakov and “A Fable” by W. Faulkner - Алексеева, Нина Симоновна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article goes about the typological correlations in M. Bulgakov’s “The Master and Margarita” and W. Faulkner’s “A Fable”, namely about the typology of the narrative model “text in the text”. It is argued, that the matrix (external) texts of both novels are of publicist character. As for the embedded (internal) texts, Bulgakov’s one has a sense-generating, nuclear potential, while in Faulkner this text fulfills the complementary function, contributing to the meaning of the external text. It is proved in the research that both texts in these novels incorporate the theme of love that, in our view, is the fictional response to the existential pattern and tragic character of the XXth century.